HBs antigen and mannose loading on the surface of iron oxide nanoparticles in order to immuno-targeting: fabrication, characterization, cellular and humoral immunoassay - Mahsa Rezaei; Seyed Nezamedin Hosseini; Ramazan Ali Khavari-Nejad; Farhood Najafi; Mehdi Mahdavi (Artificial Cells, Nanomedicine, and Biotechnology)
Mannosylation of nanovaccine is an appropriate strategy for targeting the mannose receptors on DCs. Here, HBsAg and mannose loaded on the surface of iron oxide nanoparticles to increases HBsAg vaccine potency. Nanoparticles are made by co-precipitation method and bonded to the HBsAg and mannose by chemical bonding. The physicochemical properties of nano-vaccines, their toxicity and antigenicity were determined. The synthesized nano-vaccine showed spherical shape with a mean particle size of 60 nm, a zeta potential of −44 mV, an antigen-binding efficiency of around 100% and for mannose 78%. In vitro release of nanoparticles exhibited about 30% at the first day and about 60% until the third day. SDSPAGE analysis confirmed structural integrity of HBsAg loaded on nanoparticles. The HBsAg-loaded LCMNP and MLCMNP nanoparticles had no toxic effects on HEK293 cell line. The quantification of the intracellular Fe by ICP-OES as a criterion of nano-vaccine uptake revealed mannose intensify uptake of MLCMNP. In addition, mannose in the structure of MLCMNP improved IL-6, TNF-α and IFN-γ (>16 fold) cytokines genes expression by macrophage/dendritic cells after exposure in 12 h. Immunization of experimental mice (subcutaneously, two times with 2-week intervals) with 5 µg of HBsAg loaded on MLCMNP nanoparticles increased specific total IgG and IgG2a/IgG1 ratio. In addition, TNF-α, IL-12, IL-2 and IL-4 cytokines in mannosylated nano-vaccine increased versus nano-vaccine group while lymphocyte proliferation and IFN-γ responses in the targeted nano-vaccine group show a tiny increase versus the nano-vaccine group. The results show that mannosylated nano-vaccine promotes higher level of cellular and humoural immune responses against HBsAg nano-vaccine.